Backlash Control and the Fatigue Life Bench Test of Bevel Gears from Inter-axle Differential - Zhao Long; Liu Hu; Zhang Lingxiao; Wang Hao (Jixie chuandong)
The bevel gears are the core components of inter-axle differential. The reliability of the bevel gears will affect the differential function and transmission capacity between different drive axles. Focusing on improving the fatigue life of bevel gears from the point of gears' backlash control, the issue that the selection of backlash for bevel gears are ambiguous during the actual application is resolved. Adopting a modular design concept, establish a backlash control dimension chain, and propose a method of adding steps on the input shaft to accurately control the backlash of bevel gears; through the fatigue life test rig of the interaxle differential bevel gear, the optimal control range for the total backlash of the interaxle differential bevel gear is explored to be [0.30, 0.60] mm; it is known that the change in backlash has a significant impact on the contact fatigue life of bevel gears and the bending fatigue life of tooth roots, and reasonable backlash control can increase the contact fatigue life of tooth surfaces by 29%. The research provides theoretical and experimental basis for improving the fatigue life of bevel gears in the inter axle differential.